Non-driven Micromechanical Gyroscopes and Their Applications - Zhang, Fuxue (Springer Berlin Heidelberg, 2018)
This book comprehensively and systematically introduces readers to the theories, structures, performance and applications of non-driven mechanical and non-driven micromechanical gyroscopes. The book is divided into three parts, the first of which mainly addresses mathematic models, precision, performance and operating error in non-driven mechanical gyroscopes. The second part focuses on the operating theory, error, phase shift and performance experiments involving non-driven micromechanical gyroscopes in rotating flight carriers, while the third part shares insights into the application of non-driven micromechanical gyroscopes in control systems for rotating flight carriers. The book offers a unique resource for all researchers and engineers who are interested in the use of inertial devices and automatic control systems for rotating flight carriers. It can also serve as a reference book for undergraduates, graduates and instructors in related fields at colleges and universities.